Intersectionality of disability and cultural/linguistic diversity in the UK: a literature review - Kaplan, Gamze; Celik, Pinar (Frontiers in Education, 2023)
This article explores the intersectionality of cultural and linguistic diversity and having a child with a disability, highlighting the unique challenges faced by parents from a minority ethnic background at this intersection. With increasing globalisation, diverse and multicultural populations have become more prevalent, necessitating inclusive systems that address the unique needs of minority ethnic groups. Understanding the experiences of parents at the intersection of cultural and linguistic diversity and having a child with a disability is crucial for providing equitable access to education and support. This paper provides an overview of studies conducted in the UK, focusing on the challenges faced by culturally and linguistically diverse families from a minority ethnic background with children with disabilities and emphasising factors such as religion, cultural beliefs, language barriers, and unique insights into specific populations. The findings emphasise the need for a comprehensive understanding of the intersectionality of cultural and linguistic diversity and disability to create inclusive educational environments that empower all children, irrespective of their cultural background or abilities. The aim of this paper is to provide a review of the research that describes the views and experiences of parents in the UK who are at the intersection of being from minority backgrounds and having a child with a disability regarding the concept and identification of disability, as well as their experiences and challenges while accessing services.The concept of intersectionality was introduced by the legal scholar and critical race theorist Kimberlé Crenshaw.